Web design : - Shelly, Gary B. (Course Technology, 2006)
This second edition explains the connection between a detailed design plan that considers audience needs, site purpose, and various technical issues of a successful Web site. Written for an introductory course, the text offers a variety of challenging written and hands-on activities at the end of each chapter that test comprehension, build Web research skills and design awareness, and provoke thought regarding current issues in technology. Web Design, Second Edition reveals useful design concepts and techniques typically not addressed in HTML or Web authoring texts, and is written in a style that makes the concepts and techniques presented easy to understand.